Microbial model of Halobacterium salinarum for screening inhibitors of sterol biosynthesis - A. S. Trenin (Антибиотики и Химиотерапия, 2020)
A highly effective and simple microbial test system for screening inhibitors of sterol biosynthesis (ISB) is described. The system is based on cultivation of the bacterial strain Halobacterium salinarum (former Halobacterium halobium), that possesses mevalonate pathway of sterol biosynthesis and is much similar in the biosynthesis to cholesterol formation in humans. In the H.salinarum test system the ISB were found as compounds that inhibited the test culture growth. Mevalonate which is one of the crucial intermediates of sterol biosynthesis dismissed the inhibitory effect of many microbial metabolites thus being evident of their action at the early stages of the sterol biosynthesis, including the HMG-CoA reductase stage. The H.salinarum test system was developed as a micromethod and could be easily mechanized by miniaturization of the microbiological procedures, cultivation in sterile 96-well plates and using automatic micropipettes and dispensers. The H.salinarum test system was effective in testing crude extracts of the culture broths and advantageous at early stage of screening. The use of the H.salinarum test system was shown possible for screening antitumor antibiotics.